TiO2 thin films by ultrasonic spray pyrolysis as photocatalytic material for air purification - Ibrahim Dundar (Royal Society Open Science, 2019)
In this study, we showed that the TiO2 thin films deposited onto window glass are practicable for air purification and self-cleaning applications. TiO2 films were deposited onto window glass by ultrasonic spray pyrolysis method. Different deposition temperatures were used in the range of 250–450°C. The structural, morphological, optical properties and surface chemical composition were investigated to understand probable factors affecting photocatalytic performance and wettability of the TiO2 thin films. The TiO2 thin films were smooth, compacted and adhered adequately on the substrate with a thickness in the range of 100–240 nm. X-ray diffraction patterns revealed that all the TiO2 thin films consisted of anatase phase structure with the mean crystallite size in the range of 13–35 nm. The optical measurements showed that the deposited films were highly transparent (approx. 85%). The wettability test results showed that the TiO2 thin films sprayed at 350°C and 450°C and annealed at 500°C for 1 h were superhydrophilic. The photocatalytic activity of the films was tested for the degradation of methyl tert-butyl ether (MTBE) in multi-section plug-flow reactor. The TiO2 film deposited at 350°C exhibited the highest amount of conversion of MTBE, approximately 80%.